Erotismo moderno en literatura antigua. Ejemplos en los cancioneros castellanos del siglo XVI - Schatzmann, Martin (Revista de Filología Románica, 2006)
Eroticism is already established as a serious field of literary research, contributing new material as well as new aspects of known works. The studies about the Golden Age have already proofed that the image of Spain as dominated by censorship and religion is only very partial. The best known and studied as well as most published aspect of sensual love is the eroticism jocular of the erotic-burlesque poetry. Although very common it is not the only form of expressing sensuousness in the Golden Age. Here I contribute and analyze examples to demonstrate that also Golden Age has known sensual verses that can be called erotic in the most modern sense of the word without being centred in laughter. The latter is precisely the main difference from what we consider as erotic today. Being eroticism a sensitive subject it illustrates especially well, how the approach of the researcher restricts actually the vision of the whole.